Development of a Reference Handbook Based on Contextual Teaching Learning in Curriculum Studies Course - Beta Wulan Febriana; Widinda Normalia Arlianty (International Journal of Chemistry Education Research, 2018)
ABSTRACT: The study aims to find out the implementation of reference handbook based on CTL. Design of the study is a modified Research and Development (R&D) developed by Borg and Gall. Subjects in this study are students of Chemical Education Major in Islamic University of Indonesia in the odd semester of academic year 2016/2017. The reference handbook arranged has been validated by academics and practitioners and categorized as "Very Good" with score 92.29% and 92.09% respectively. Furthermore, the reference handbook was also tested in the Preliminary Field Testing phase and scored 88.89% with the category "Very Good". After the reference handbook was revised following the phase, it was re-tested at the Main Field Testing phase and scored 89.09% with the category "Very Good". Based on these results, the reference handbook has been developed can be implemented in the Curriculum Studies course very well.Keywords: curriculum studies, contextual teaching and learning (CTL), reference handbookReceived: 9 January 2018, Revised: 22 January 2018, Accepted 24 February 2018